FEATURES OF FORMATION OF LOCAL BUDGET INCOME IN THE CONDITIONS OF BUDGET DECENTRALIZATION - Shchur, R.I.; Zvarych, T.Ya. (The actual problems of regional economy development, 2017)
In the article the theoretical aspects of definition of the essence of the concept of “budget decentralization” are considered, the main stages of formation of a decentralized state are considered. The structure and dynamics of revenues of local budgets of Ivano-Frankivsk region from 2010 to 2016 are analyzed. The level of implementation of the revenue of local budgets, as well as the peculiarities of their formation and conditions of budget reform in Ukraine is analyzed.